The biological standard of living in Europe during the last two millennia - Nikola Köpke; Jörg Baten (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
This paper offers the first anthropometric estimates on the biological standard of living in central Europe in the first millennium, and expands the literature on the second millenium. The overall picture is one of stagnant heights. There was not much progress in European nutritional status, not even between 1000 and 1800, when recent GDP per capita estimates arrive at growing figures. We find that heights stagnated during the Roman imperial period in Central, Western and Southern Europe. One astonishing result is the height increase in the fifth and sixth centuries. Noteworthy is the synchronicity of the height development in three large regions of Europe. In a regression analysis of height determinants, population density was clearly economically (but not statistically) significant. Decreasing marginal product theories and Malthusian thought cannot be denied for the pre-1800 period. Of marginal significance were climate (warmer temperatures were good for nutritional status), social inequality and gender inequality (both reduce average height).
urn:nbn:de:bsz:21-opus-18642
Keywords: 330; Lebensstandard; Ernährung; Gesundheit; Europa